PENGARUH PELATIHAN SDM DAN MANAJEMEN REKRUTMEN TERHADAP RETENSI KARYAWAN PADA PT AGUNG PODOMORO LAND TBK. JAKARTA BARAT - Imelda Febriana; Iskandar Zulkarnain (Al Hasanah Barokah Foundation, 2026)
This study aims to determine the extent to which human resource training and recruitment management influence employee retention at PT Agung Podomoro Land Tbk. West Jakarta. The method used is a quantitative approach with data collection techniques through distributing questionnaires to 55 respondents. Data analysis was carried out through validity and reliability tests, simple and multiple linear regressions, as well as partial (t-test) and simultaneous (F-test) hypothesis tests. The results of the analysis indicate that human resource training has a positive and significant influence on employee retention, evidenced by a calculated t value of 9.369 and a significance of 0.000 (<0.05). Recruitment management does not have a partial significant effect on employee retention (calculated t = 1.005; significance = 0.325). However, simultaneously, both variables have a significant effect on employee retention with a calculated F value of 51.354 and a significance value of 0.000. The R Square value of 0.667 indicates that 66.7% of the variation in employee retention can be explained by human resource training and recruitment management, while the remaining 33.3% is influenced by other factors not studied